Síntese e atividade citotóxica de alguns azido-ciclopaladados estabilizados com ligantes bifosfínicos - Caires, Antonio Carlos Fávero; Almeida, Eduardo T. [UNESP]; Mauro, Antonio Eduardo [UNESP]; Hemerly, Jefferson P. [UNESP]; Valentini, Sandro Roberto [UNESP] (Sociedade Brasileira de Química, 1999)
Some cyclopalladated compounds containing the azido group ligand and the (C-N) ring of N,N-dimethylbenzylamine have been prepared by bridge opening reactions of dimmer azide complex precursor with some diphosphines in different stoichiometric quantities. The neutral or ionic, mono or binuclear complexes synthesized were characterized by elemental analyses, I. R. spectroscopy and NMR techniques. The series of complexes was screened for cytotoxicity against a panel three human tumour cells lines(C6,Hep-2,HeLa). All complexes were found to be cytotoxic (IC50) at µM concentrations while one complex having the coordination bond N-Pd ruptured also displayed some differential cytotoxicity.
Synthesis and cytotoxicity of some cyclometallated palladium (II) complexes containing coordinated azide and diphosphines
Keywords: azido-cyclopalladated compounds; antitumour agents; palladium (II) complexes